Comparison between weekly vs daily dosing L-thyroxine for the treatment of hypothyroidism in Ramadan - a pilot randomized controlled trial - Nurul Aulia binti Zakaria (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
INTRODUCTION: Hypothyroidism, a common endocrine disorder, also affects Muslims who fast during the month of Ramadan. Muslim who fast during Ramadan find it difficult to take Levothyroxine (L-thyroxine) as recommended every morning on empty stomach during sahur. Furthermore, the changes in eating patterns and gastric motility during Ramadan might affect the absorption and efficacy of L-thyroxine replacement. OBJECTIVE: (1)To compare the efficacy of weekly vs daily L-thyroxine dosing, in terms of changes in thyrotropin (TSH), free T4 (fT4) and free T3 (fT3) (2) To compare the frequency of side-effects of weekly vs daily dosing of L-thyroxine in Ramadan in terms of symptoms, cardiac function, lipid parameters, cognitive and psychological function. (3) To assess patient's preference of L-thyroxine dosing during Ramadan. METHOD: This is a randomized open-label controlled trial among hypothyroid patients on L-thyroxine replacement who fasted during Ramadan 2017 and 2018 in a tertiary centre located in Kuantan. Hypothyroid patients who fulfil the inclusion criteria were randomized into two arms, weekly (W) and daily (D) arm. The weekly arm took seven times their usual L-thyroxine dose at least 30 minutes pre-sahur once a week whereas the daily arm took their usual L-thyroxine dose daily at least 2 hours after their last meal before bed. Thyroid function test (TSH, fT3, fT4), cardiac parameters (electrocardiography, echocardiography and 24-hours Holter monitoring), symptoms, cognitive and psychological assessment were done at week zero, w0 (baseline). A repeat cardiac assessment was done at week 2 (w2) for the weekly arm within 24-hours of high dose L-thyroxine administration. At the end of week 4 (w4), thyroid function, lipid parameters, symptoms, cognitive and psychological assessment of both group were reassessed. Patient's preference for weekly arm were assessed on their last visit at week 4. The efficacy, safety and patient's preference were analysed. RESULTS: A total of eighteen patient were randomized into two groups (n = 9 for each arm). The median age of the patients for weekly and daily group were [W 34(27.5,48.5); D 45(36.5,51); p=0.22] with majority (66.7% each arm) were diagnosed with post-radioiodine hypothyroidism. All other parameters were comparable at baseline. At the end of study, there were no significant change in the median level of thyroid hormones for weekly arm however significant increment of TSH was observed in daily arm [TSH w0 1.8(0.23,5.57) vs w4 3.65(0.45,16.1); p= 0.011]. Thyroid hormones levels between both arms were comparable at the end of study. There was no hyperthyroid symptoms or cardiac toxicity observed despite significant increment of fT4 within 24hours of weekly dosing [fT4 w0 13.21(8.19,14.63) vs w2 17.43(12.38,22.55); p=0.011]. All patients were euthyroid and no side effects were reported at the end of study. Majority (83.3%) of patients prefer weekly dosing of L-thyroxine during Ramadan. CONCLUSION: From this pilot study, weekly L-thyroxine dosing during Ramadan appeared to be safe and efficient and was the more preferred dosing method.